1968
DOI: 10.1029/jb073i010p03247
|View full text |Cite
|
Sign up to set email alerts
|

Lengths of geomagnetic polarity intervals

Abstract: Variations in the lengths of geomagnetic polarity, intervals are analyzed by means of a probability model based on the theory of Bernouli trials. Polarity reversals are assumed to occur as the result of the interaction between steady oscillations of the geomagnetic dipole and secular variations of the nondipole field. The particular cycle on which a polarity inversion occurs is determined by the magnitude of the nondipole field, which is assumed to vary randomly and independently of dipole variations. The reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
194
0
2

Year Published

1971
1971
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 328 publications
(205 citation statements)
references
References 31 publications
9
194
0
2
Order By: Relevance
“…We have more than 30 lavas with well-defined polarity at Mahabaleshwar (Table 1), and P(T, n, 0)+P(T, n, 1) is less than 0.05 for any T larger than Although the polarity time scale for about to m.y. has been well established by the consistency of data from dated volcanic rocks, deep-sea cores and magnetic Iineation over the ocean (Cox, 1968), it is still ambiguous for the older periods. The only data we have at present come from magnetic anomaly charts from different oceans (HEIRTZLER et al, the figure indicate n. (a) P(T ; n, 0) and (b) P (T; n, 1) of 45-70 m.y.…”
Section: Estimation Of the Time Interval Of The Deccan Volcanismmentioning
confidence: 99%
“…We have more than 30 lavas with well-defined polarity at Mahabaleshwar (Table 1), and P(T, n, 0)+P(T, n, 1) is less than 0.05 for any T larger than Although the polarity time scale for about to m.y. has been well established by the consistency of data from dated volcanic rocks, deep-sea cores and magnetic Iineation over the ocean (Cox, 1968), it is still ambiguous for the older periods. The only data we have at present come from magnetic anomaly charts from different oceans (HEIRTZLER et al, the figure indicate n. (a) P(T ; n, 0) and (b) P (T; n, 1) of 45-70 m.y.…”
Section: Estimation Of the Time Interval Of The Deccan Volcanismmentioning
confidence: 99%
“…The probability density implied by Cox's (1968) model is compared with the observed data and it is shown that the data do not support this model. A statistical model is then developed in which the TDMs have a truncated Gaussian distribution, the non-dipole field strength is linearly proportional to the TDM and the palaeointensity determination itself introduces a random error with standard deviation of about 10%.…”
Section: Introductionmentioning
confidence: 99%
“…Our reason for reconsidering the question of the conservation of total energy over long periods of time is its relevance to current attempts to explain geomagnetic reversals on the basis of statistical models (Cox, 1968(Cox, , 1969Nagata, 1969;Parker, 1969). In these models, cyclonic convection cells in the core produce reversals by a two-step mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In the models of Nagata (1969) and Parker (1969) the occurrence of a reversal depends only on the spatial distribution of cyclones and not on the intensity of the dipole field. In the model of Cox (1968), the occurrence of reversals depends both on the distribution of cyclones and on the field strength of the cyclonic disturbances (i.e. , nondipole field) relative to the dipole field.…”
Section: Introductionmentioning
confidence: 99%